Desenvolvimento de um smart meter: um estudo sobre eficiência energética através das redes inteligentes - Amaral, Haroldo Luiz Moretti do [UNESP] (2014)
The smart grids and smart meters become a reality closer to residential consumers worldwide. Several countries are developing studies with focus on impacts related to the introduction of these new technologies and energy efficiency is one of the major objectives to be achieved. Gains related to energy efficiency will be felt directly by the consumer through the economy in electricity bills. Will also be noted by the concessionaires by minimizing transmission and distribution losses, by the increased system stability, minimizing the load during peak hours, among others. To demonstrate the potential of energy efficiency will be presented two references, one focusing on the introduction of smart meters and their interfaces with users and other relating the smart grids and new concepts such as demand response. The smart meters are the basis for the implementation of the smart grids, and are indispensable to conducting tests as presented. There are many electronic meters as well as educational kits for development available in the market, however, depending on the application may become limited or inflexibe regarding to modifications. Finally it is presented the development of a low cost smart meter, with a flexibe structure, aiming to achieve accuracy and precision in the measurements plus the ability to store the collected data, allowing further analysis. The smart developed achieved it objectives and proved to be a very interesting tool to monitor the network and also the behavior of consumers